Predictive and prognostic values of ERCC1 and XRCC1 in biliary tract cancers. Issue 8 (13th January 2016) - Mian, Muhtashim; McNamara, Mairéad G; Doherty, Mark; Hedley, David; Knox, Jennifer J; Serra, Stefano
Abstract : Aims: To investigate the predictive and prognostic values of DNA repair genes excision repair cross-complementation group 1 ( ERCC1 ) and X-ray repair cross-complementing group 1 ( XRCC1 ) in tumour samples from patients with a diagnosis of biliary tract cancer (BTC). Methods: Expressions of ERCC1 and XRCC1 were determined by immunohistochemistry (IHC) for 160 patients with BTC and association with clinicopathological features and patient survival was performed to evaluate their predictive and prognostic values. Results: Neoplastic tissue showed much lower nuclear expression compared with non-neoplastic tissue for ERCC1 (median immunostaining score (IS)=0.7 (95% CI 0.2 to 1.3) vs 8.0 (95% CI 5.5 to 8.0), p<0.001) and XRCC1 (median IS=4.0 (95% CI 3.0 to 5.5) vs 8.0 (95% CI 8.0 to 12.0), p<0.001). High nuclear expression of both proteins was able to predict better overall survival (OS) in patients with gallbladder adenocarcinoma, distal bile duct and perihilar cholangiocarcinoma undergoing gemcitabine as adjuvant therapy (ERCC1: median OS estimate=39.7 vs 22.9 months, p=0.011; XRCC1: median OS estimate=33.8 vs 14.6 months, p=0.005). Intense cytoplasmic expression of XRCC1 was found in 12 patients; these patients had significantly more frequent lymph node metastasis (90.0% vs 48.1%, p=0.017) and worse OS (median estimate=12.6 months vs 25.6 months, p=0.004) and recurrence-free survival (median estimate=5.7 months vs 15.1 months, p=0.011). Vascular invasion was significantly more frequent in patients with low nuclear expression for ERCC1 (58.7% vs 20.9%, p<0.001) and XRCC1 (69.6% vs 30.3%, p=0.001). Conclusions: IHC expression of ERCC1 and XRCC1 has some predictive and prognostic values in patients with BTC. Nuclear expression of ERCC1 and XRCC1 may be used to predict therapeutic response in patients undergoing gemcitabine monotherapy.